2002
DOI: 10.1007/s380-002-8317-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term renal sympathetic denervation on heart failure after myocardial infarction in rats

Abstract: The purpose of the present study was to investigate the effects of long-term renal denervation (RD) on heart failure due to myocardial infarction (MI). Wistar rats were anesthetized and the bilateral renal nerves were surgically denervated 2 days before MI was induced by coronary artery ligation. Four weeks later, left ventricular (LV) function and sodium excretion were determined. In MI rats, RD improved the reduced sodium excretion. MI + RD rats revealed lower LV end-diastolic pressure and greater maximum dP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 37 publications
2
60
0
2
Order By: Relevance
“…Recently, the therapeutic value of renal denervation in heart failure was evaluated in a similar experimental model of coronary ligation-induced myocardial infarction in rats. 45 This study, in which renal denervation was performed before onset of myocardial infarction, demonstrated reduced ventricular filling pressure and improved ventricular function compared with nondenervated controls. As in hypertension, deliberate renal denervation has been exploited to gain physiological insights into pathological conditions.…”
Section: Postmyocardial Infarction and Congestive Heart Failurementioning
confidence: 70%
“…Recently, the therapeutic value of renal denervation in heart failure was evaluated in a similar experimental model of coronary ligation-induced myocardial infarction in rats. 45 This study, in which renal denervation was performed before onset of myocardial infarction, demonstrated reduced ventricular filling pressure and improved ventricular function compared with nondenervated controls. As in hypertension, deliberate renal denervation has been exploited to gain physiological insights into pathological conditions.…”
Section: Postmyocardial Infarction and Congestive Heart Failurementioning
confidence: 70%
“…156,157 Davies et al 158 have recently reported the results of a pilot study of 7 patients with chronic systolic HF, who underwent bilateral renal denervation and were followed up for 6 months. The study found no procedural or postprocedural complications.…”
Section: Use Of Devices To Modulate Autonomic Nervous System In Hfmentioning
confidence: 99%
“…The reduction in sympathetic activity with renal sympathetic denervation might be expected to have similar benefits. Not surprisingly, decreased left ventricular filling pressures and improved left ventricular systolic function has been demonstrated following renal denervation in rats (47). Future studies will provide a better understanding of renal sympathetic denervation and the subsequent changes in heart failure pathophysiology.…”
Section: Future Directionsmentioning
confidence: 88%